Understanding the long-term policy influence strategies of the tobacco industry: two contemporary case studies. Issue 2 (3rd March 2022) - Hird, Thomas R; Gallagher, Allen William Andrew; Evans-Reeves, Karen; Zatoński, Mateusz; Dance, Sarah; Diethelm, Pascal A; Edwards, Richard; Gilmore, Anna B
Abstract : Objective: This paper explores transnational tobacco companies' (TTCs) long-term policy influence strategies using two case studies, harm reduction and illicit tobacco, to identify lessons for the tobacco control movement and wider efforts to address the commercial determinants of health. Methods: Evidence from a broad combination of sources including leaked documents and findings from over two decades of TTC monitoring were reviewed for each case study and categorised using the Policy Dystopia Model, focusing on the primary discursive strategy and key instrumental (action-based) strategies used. Results: In both case studies, TTCs seek to advance their interests by engaging primarily in reputation management, coalition management and information management strategies over the long-term to propagate their over-riding discursive strategy—'we've changed, we are part of the solution'—despite clear evidence from both case studies that this is not the case. These strategies are globally coordinated and attempt primarily to reshape norms towards TTC involvement in tobacco control policy and delivery. Findings also suggest that industry denormalisation and the advent of Article 5.3 have led to the TTCs growing use of increasingly complex and opaque 'webs of influence'. Conclusions: The tobacco control community must develop its own proactive long-term strategies which should include industry denormalisation, new ways to fund research that reduce industry control, and improved transparency measures for research and policy. These findings, including TTC adaptations to Article 5.3, also indicate the need for more structural solutions, addressing corporate power and the underlying political and economic system. These lessons can be applied to other unhealthy commodity industries.